Impact of pre‐examination video education in Gd‐EOB‐DTPA‐enhanced liver MRI: A comparative study - Hongfang Huang; Chenhui Li; Zisan Zeng; Junli Liang (Journal of Medical Radiation Sciences)
Abstract Introduction Hepatocellular carcinoma (HCC) is a leading cause of cancer‐related mortality, and early diagnosis via gadolinium ethoxybenzyl‐diethylenetriamine pentaacetic acid (Gd‐EOB‐DTPA)‐enhanced magnetic resonance imaging (MRI) significantly impacts patient outcomes. However, patient anxiety during MRI can affect image quality. This study investigates the impact of pre‐examination video education on anxiety, satisfaction and image quality in Gd‐EOB‐DTPA‐enhanced liver MRI. Methods We prospectively enrolled 480 patients who underwent Gd‐EOB‐DTPA‐enhanced liver MRI from January 2022 to May 2023 at our hospital. Patients were divided into study and control groups in order of odd and even days, with 240 cases in each group. Before the examination, the radiology staff provided routine verbal guidance and breathing training to the patients in the control group, while the study group was given additional video education. The state anxiety scores, satisfaction scores of the provided information and motion artefact scores of the images before and after the examination were compared between the two groups. Results The state anxiety scores of both groups of patients were lower than before the examination (all P < 0.05), but the change value of the study group was significantly greater than that of the control group (P = 0.004). The satisfaction rate of the information provided before the scan in the study group was significantly higher (P < 0.001). The image quality scores of the arterial phase were similar between the two groups (P = 0.403), but the image quality of the study group in the pre‐contrast, portal phase, transitional phase and hepatobiliary phase was significantly better than that of the control group (all P < 0.05). Conclusion Supplementing routine pre‐scan care with video guidance for Gd‐EOB‐DTPA‐enhanced liver MRI offers several benefits, including reduced patient anxiety, increased satisfaction and improved image quality. These results suggest the potential for widespread application of video‐based interventions to enhance the MRI experience for patients.